Melamine and cyanuric acid co-exposure causes renal dysfunction and structural damage via MAPKs and mitochondrial signaling. (October 2016) - Lee, In-Chul; Ko, Je-Won; Park, Sung-Hyeuk; Shin, In-Sik; Moon, Changjong; Kim, Sung-Ho; Kim, Yun-Bae; Kim, Jong-Choon
Abstract: Both melamine and cyanuric acid have low toxicity, but combined exposure to melamine and cyanuric acid (M + CA) was reported to cause unexpected toxicological synergy on kidney damage. In this study, we investigated the role of oxidative stress and apoptotic changes in the nephrotoxicity caused by M + CA in rats. M + CA treatment caused an increase in the kidney weight, serum blood urea nitrogen or creatinine levels in a dose-dependent manner. With severe morphological and histological changes in kidneys, M + CA markedly elevated lipid peroxidation and suppressed antioxidant enzyme activities. M + CA treatment induced apoptotic changes in renal tubular cells. Additionally, exposure to M + CA increased phosphorylation of mitogen-activated protein kinases (MAPKs) coincided with increased Bax level and decreased Bcl2 level, resulting in caspase-3 activation. In summary, oxidative stress and simultaneous MAPKs and mitochondrial/caspase activation may be related to renal tubular cell apoptosis caused by M + CA. Highlights: M + CA caused functional and histopathological alteration in the kidneys. M + CA increased lipid peroxidation and decreased antioxidant enzyme activities in the kidneys. M + CA induced renal tubular cell apoptotic changes in the kidneys. M + CA caused phosphorylation of mitogen-activated protein kinases (MAPKs). M + CA increased Bax and decreased Bcl2 levels with caspase-3 activation in the kidneys.